Charles Dickens and William Thackeray: two styles of one genre, one period - Abdujalil Maxmutovich, Qurbonov; Norjon Nematovna, Gafurova; Nozgul Nabiyevna, Siddiqova; Raxima Fayzulloevna, Norova (International Journal of Psychosocial Rehabilitation, 2020)
Although Charles Dickens and William Thackeray are ways of writing realism, they see the characters differently. It is therefore not an exaggeration to say that the writers of the nineteenth century had their place in English literature as writers who formed their own realism. Dickens and Thackeray created their own unique, uniquely identifiable 19th-century English characters, though they did not interrupt the classification of heroes in their works. As for Oliver Twist, for example, the protagonist named Oliver was originally thought of as a criminal detective.